The Effect of Capital Intensity, Transfer Pricing, and Sales Growth On Tax Avoidance with Company Size as A Moderation Variable - Pembayun Khamisan, Mayang Sekar; Dwi Astuti, Christina (Devotion : Journal of Research and Community Service, 2023)
This study aims to obtain empirical evidence regarding the effect of capital intensity, transfer pricing, and sales growth on tax avoidance with firm size as a moderating variable. The companies used in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) with a research period of 2018-2021. The number of research samples used was 124 data. The sampling method used was purposive sampling. This study shows the results that capital intensity and sales growth have a positive effect on tax avoidance, while transfer pricing has no effect on tax avoidance. Firm size is able to weaken the effect of capital intensity and sales growth on tax avoidance. Firm size is unable to moderate the effect of transfer pricing on tax avoidance